Legal Protection of Electronic Land Certificates in the Implementation of Ministerial Regulation ATR/BPN No. 1 of 2021 A Case Study at the Bogor City Land Office - Ahim Ahim; Desty Anggie Mustika; Annisa Aminda (Universitas Ibn Khaldun Bogor, 2026)
This study examines the legal protection aspects of electronic land certificates under the implementation of Ministerial Regulation ATR/BPN No. 1 of 2021 at the Bogor City Land Office. Employing a qualitative descriptive approach with an empirical juridical method, the research analyzes normative foundations, implementation mechanisms, and practical challenges. Data were collected through interviews, field observations, and literature review. The findings reveal that electronic certificates possess strong legal legitimacy supported by digital signatures and encrypted data storage. However, several obstacles remain, including inadequate digital infrastructure, limited digital literacy among the public, and concerns about cybersecurity. Strengthening legal frameworks, improving technical readiness, and increasing public awareness are essential to ensuring effective legal protection and public trust in the digital land administration system.